What increase students’ creative thinking skills? employing problem-based learning-digital mind map in biology learning - Zia Aulia Zaidin Putra; I. Ibrohim; Herawati Susilo; Hadi Suwono (Research and Development in Education (RaDEn), 2024)
Creative thinking has widely discussed due the urgency at the 21st century life. These thinking process helps people to tackling situation and problems in daily life. This study aimed to analyze the secondary students’ creative thinking through Problem-based Learning integrated with Digital Mind Map (PBL-DMM). This study was conducted at Solok Secondary High School, West Sumatra, Indonesia. Using quantitative research design, 60 students were taught by PBL-DMM. Creative thinking was testing by essay test in three times. The essay tests previously validated by the expert appraisal and once were testing to the former students to measure the empirical validity and reliability. All tests were declared valid and reliable. The result of the treatment was students’ creative thinking increase within three time of tests. This finding means that PBL-DMM can helps students to promote their creative thinking during the learning process. Digital mind map taking role as a tool to organize students’ concept, knowledge, and information.